Transformasi Digital UMKM Indonesia : Tantangan dan Strategi Adaptasi di Era Ekonomi Digital - Putri Sandrina Sitompul; Maya Martiza Sari; Cecillia Miranda Br Lumban Gaol; Lokot Muda Harahap (Jurnal Manajemen Bisnis Digital Terkini, 2025)
The digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is crucial for enhancing competitiveness and sustainability in the digital economy era. However, MSMEs face significant challenges, including low digital literacy, limited financial resources, uneven digital infrastructure, and insufficient regulatory support. This study aims to analyze these challenges and propose adaptation strategies through a qualitative literature review approach. Data were collected from credible sources, including academic journals, government reports, and reputable articles, focusing on the period from 2019 to 2024. The findings highlight the importance of external support, such as training, mentoring, and government policies, in facilitating digital transformation. Key strategies include improving digital literacy, collaborating with digital platforms, and fostering product innovation. The study also emphasizes the need for government intervention in infrastructure development and policy reform to create a conducive ecosystem for MSMEs. While digital transformation offers significant benefits, such as operational efficiency, market expansion, and increased competitiveness, the digital divide between urban and rural MSMEs remains a critical issue. This research provides recommendations for stakeholders to ensure inclusive and sustainable digital transformation for all MSMEs in Indonesia.